Problem Diagnosis and Research Prioritisation of Sweet Potato in India - Mathevanpillai, Ananatharaman; Subramanian, Ramanathan; Paramasivan, Sivakumar Sethuraman; Tavva, Srinivas; Maniyam, Nedunchezhiyan (JOURNAL OF ROOT CROPS, 2015)
Sweet potato (Ipomoea batatas) is one of the world’s most important food crops in terms of human consumption, particularly in Sub-Saharan Africa, parts of Asia and the Pacific Islands. The major sweet potato growing countries are China, Uganda, Nigeria, Indonesia and Vietnam. In India, it is cultivated in many states, but a relatively more concentration of this is found in Odisha, Uttar Pradesh, Bihar, Jharkhand and West Bengal. It is cultivated in an area of 0.113 m ha in India in various types of production systems. In order to have need based problem oriented research programmes on sweet potato and to utilise the limited resources effectively, an attempt was made to diagnose the problems and prioritisation of the researchable issues aimed to solve the problem. Problem diagnosis of sweet potato was carried out in Odisha, Uttar Pradesh, West Bengal and Kerala using participatory appraisal tools like key informant technique and focused group discussion. The major problems diagnosed were (i) Sweet potato is suitable for kharif only, difficult to cultivate in rabi in view of other competitive crops like potato, carrot etc. (ii) Competitive crops like vegetables are remunerative than sweet potato (iii) Lack of appropriate high yielding varieties (iv) Hybrid varieties are prone to sweet potato weevil (SPW) and (v) SPW menace, if harvested late (after 120 days). Based on the problems, 53 researchable ssues were identified initially, which were subjected to judges rating for their importance, which resulted in narrowing down to 15 issues. These issues were analysed for Net Present Value (NPV), Benefit:cost Ratio (BCR), Internal Rate of Returns (IRR) and issues were prioritised as follows (i) Seasonal effects on tuberisation (ii) Germplasm collection (iii) Technology transfer (iv) Quality seed production, distribution and seed system studies (v) Stable high yield weevil tolerant varieties (vi) Integrated Pest Management (IPM) of SPW and (vii) Lowering the cost of production and (viii) Exploring exclusive value added products.